2010
DOI: 10.1002/jssc.201000572
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of synthetic copolymers by interaction polymer chromatography: Separation by microstructure

Abstract: Gradient elution of synthetic polymers has been studied both theoretically and experimentally using normal and reversed-phase HPLC systems. An accurate equation describing the gradient elution of polymer-homologous series in the context of continuous random-flight model of a flexible polymer chain interacting with attractive surface of the porous material has been derived and experimentally verified against a series of narrow polystyrene standards. Both the theory and the experiment predict the existence of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…Statistical polymers behave like a homopolymer in chromatography, equivalent to homopolymer of some effective segment that is repeated throughout the chain. 50,51 In this particular case, EC-EE-EE might behave as an effective repeat unit, Figure 2(C). To the best of our knowledge, this is the first report of critical adsorption point of PEEC.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Statistical polymers behave like a homopolymer in chromatography, equivalent to homopolymer of some effective segment that is repeated throughout the chain. 50,51 In this particular case, EC-EE-EE might behave as an effective repeat unit, Figure 2(C). To the best of our knowledge, this is the first report of critical adsorption point of PEEC.…”
Section: Resultsmentioning
confidence: 98%
“…The successful establishment of critical conditions of the polymer endorse the NMR results. Statistical polymers behave like a homopolymer in chromatography, equivalent to homopolymer of some effective segment that is repeated throughout the chain . In this particular case, EC–EE–EE might behave as an effective repeat unit, Figure (C).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to recall the behavior expected for block copolymers under GPEC conditions. A key paper is the work published by Brun and Foster []. They showed that in the case of a diblock copolymer, both the monomer ratio and the molecular weight of the polymer will determine elution time.…”
Section: Discussionmentioning
confidence: 99%
“…The RAFT mechanism shown in Figure 2.1 helps to describe the essential problem for reinitiation and propagation of a new block from a thiocarbonylthio-functionalized first block. IPC separates macromolecules by chemical composition as well as by individual block length, so that compositional uniformity of the copolymer can be estimated (Brun and Foster, 2010). Such competing processes were recognized early in the development of RAFT (Mayadunne et al, 2000b).…”
Section: Dsa Applicationsmentioning
confidence: 99%